Eating Habits Associated with Overweight and Obesity: A Case-control Study of 11-14 Year-old Adolescents in Hanoi - Thi Hong Hanh, Nguyen; Thi Thu Hang, Tran; Hong Lam, Pham; Nam Khanh, Duong; Hoang Ngoc Ha, Do (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 37 No 1DO - 10.25073/2588-1132/vnumps.4280, 2021)
This study analyzes the association of eating habits with overweight and obesity among adolescents at the age of 11-14 from 9 junior high schools in Hanoi to help design a model for predicting overweight and obesity resulted from eating habits. A case-control study was conducted on 222 overweight/obese adolescents and 616 normal-weight adolescents (according to the International Obesity Taskforce Standards, IOTF). The research results show that protective factors of overweight and obesity include snacking (snacking at least 2 hours before or after a main meal), consumption of milk and dairy products in snacks, and sensory liking for fruit. Risk factors include sensory liking for: fat, sweet, fast food, carbonated soft drinks; skipping breakfast; and snacking before bed. The best predictive model of overweight and obesity is built from logistic regression analysis including 8 of the above eating habits with AUC (Area under the Curve) value of 0.931. The study concludes that eating habits are closely related to overweight and obesity among 11-14 year-old adolescents in Hanoi. Keywords Eating habits, overweight, obesity, adolescence, risk factor. References [1] A.S. French, M. Story and C.L. Perry, Self-esteem and obesity in children and adolescents: a literature review, Obesity Research 3 (1995) 479-490. https://doi.org/10.1002/j.1550-8528.1995.tb00179.x [2] E.A. Finkelstein, C.J. Ruhm, and K.M. Kosa, Economic causes and consequences of obesity, Annual Review of Public Health 26 (2005) 239-257. https://doi.org/10.1146/annurev.publhealth.26.021304.144628   [3] N.T.H. Hanh, L.T. Tuyet, D.T.A. Dao, Y. Tao, and D.T. Chu, Childhood obesity is a high-risk factor for hypertriglyceridemia: a case-control study in Vietnam, Osong public health and research perspectives 8 (2017) 138-146. https://doi.org/10.24171/j.phrp.2017.8.2.06 [4] J.K. Dibaise, and A.E. Foxx-Orenstein, Role of the gastroenterologist in managing obesity, Expert Review of Gastroenterology & Hepatology (Review) 7 (2013) 439-451 https://doi.org/10.1586/17474124.2013.811061 [5] P.V.N. Nguyen, T.K. Hong, T. Hoang, and A.R. Robert, High prevalence of overweight among adolescents in Ho Chi Minh City, Vietnam, BMC Public Health 13 (2013) 141-147. https://doi.org/10.1186/1471-2458-13-141 [6] T.T.P. Pham, Y. Matsushita, L.T.K. Dinh, T.V. Do, T.T.T. Nguyen, A.T. Bui, A.Q. Nguyen, and H. Kajio, Prevalence and associated factors of overweight and obesity among schoolchildren in Hanoi, Vietnam, BMC public health 19 (2019) 1478-1488. https://doi.org/10.1186/s12889-019-7823-9 [7] H.D. Phan, T.N.P. Nguyen, P.L. Bui, T.T. Pham, T.V. Doan, D.T. Nguyen, and H.V. Minh, Overweight and obesity among Vietnamese school-aged children: National prevalence estimates based on the World Health Organization and International Obesity Task Force definition, PloS one 15 (2020) e0240459-e0240478. https://doi.org/10.1371/journal.pone.0240459 [8] M. Zalewska, and E. Maciorkowska, Selected nutritional habits of teenagers associated with overweight and obesity, PeerJ 5 (2017) e3681-e3693. https://doi.org/10.7717/peerj.3681 [9] K. Sygit, W. Kollataj, M. Gozdziewska, M. Sygit, B. Kollataj, and I.D. Karwat, Lifestyle as an important factor in control of overweight and obesity among schoolchildren from the rural environment, Annals of Agricultural and Environmental Medicine 19 (2012) 557-561. PMID: 23020056. https://journals.indexcopernicus.com/search/article?articleId=2116928 [10] N.V. Tuan, Evidence-Based Medicine, Medical publisher, Hanoi, 2008 (in Vietnamese). [11] T.J. Cole, M.C. Bellizzi, K.M. Flegal, and W.H. Dietz, Establishing a standard definition for child overweight and obesity worldwide: international survey, Bmj 320 (2000) 1240-1245. https://doi.org/10.1136/bmj.320.7244.1240 [12] L.T. Hop và Huynh Phuong Nam, Assessment of nutritional status using anthropometric variables, Journal of Food and Nutrition Sciences 7 (2011) 1-7 (in Vietnamese). [13] X. Guo, L. Zheng, Y. Li Y, S. Yu, G. Sun, H. Yang, X. Zhou, X. Zhang, Z. Sun, and Y. Sun, Differences in lifestyle behaviors, dietary habits, and familial factors among normal-weight, overweight, and obese Chinese children and adolescents, International Journal of Behavioral Nutrition and Physical Activity 9 (2012) 120-128. https://doi.org/10.1186/1479-5868-9-120 [14] J. Yoshida, E. Eguchi, K. Nagaoka, T. Ito, and K. Ogino, Association of night eating habits with metabolic syndrome and its components: a longitudinal study, BMC Public Health 18 (2018) 1366-1379. https://doi.org/10.1186/s12889-018-6262-3 [15] L.A. Spence, C.J Cifelli, and G.D. Miller, The role of dairy products in healthy weight and body composition in children and adolescents, Current Nutrition & Food Science 7 (2011) 40-49. https://doi.org/10.2174/157340111794941111 [16] R.E. Black, S.M. Williams, I.E. Jones, and A. Goulding, Children who avoid drinking cow milk have low dietary calcium intakes and poor bone health, The American journal of clinical nutrition 76 (2002) 675-680. https://doi.org/10.1093/ajcn/76.3.675 [17] I.F.F. Júnior, D.G. Christofaro, J.S. Codogno, P.A. Monteiro, L.S. Silveira, and R.A. Fernandes, The association between skipping breakfast and biochemical variables in sedentary obese children and adolescents, The Journal of pediatrics 161 (2012) 871-874. https://doi.org/10.1016/j.jpeds.2012.04.055 [18] R. Rosenheck, Fast food consumption and increased caloric intake: a systematic review of a trajectory towards weight gain and obesity risk, Obesity reviews 9 (2008) 535-547. https://doi.org/10.1111/j.1467-789X.2008.00477.x [19] A. Lampuré, K. Castetbon, A. Deglaire, P. Schlich, S. Péneau, S. Hercberg, and C. Méjean, Associations between liking for fat, sweet or salt and obesity risk in French adults: a prospective cohort study. International Journal of Behavioral Nutrition and Physical Activity 13 (2016) 74-88. https://doi.org/10.1186/s12966-016-0406-6 [20] H.C. Hung, K.J. Joshipura, E. Jiang, F.B. Hu, D. Hunter, S.A. Smith-Warner, G.A. Colditz, B. Rosner, D. Spiegelman, and W.C. Willett, Fruit and vegetable intake and risk of major chronic disease, Journal of the National Cancer Institute 96 (2004) 1577-1584. https://doi.org/10.1093/jnci/djh296 [21] D.S. Eweis, F. Abed, and J. Stiban, Carbon dioxide in carbonated beverages induces ghrelin release and increased food consumption in male rats: implications on the onset of obesity, Obesity research & clinical practice 11 (2017) 534. https://doi.org/10.1016/j.orcp.2017.02.001 [22] M.K. Siddiqui, R. Morales-Menendez, and S. Ahmad, Application of receiver operating characteristics (ROC) on the prediction of obesity, Brazilian Archives of Biology and Technology 63 (2020) e20190736-e20190749. http://dx.doi.org/10.1590/1678-4324-2020190736